Investigation and analysis of finding the injection molding gate by using moldflow - Muhamad Fridy Nizam, Harun (2007)
Demand on plastic product in this country is very tremendous because plastic product has better in quality, design and appearance than any material product. To produce better quality of plastic product, it needs to have some processes and most important is initially in design stages. The design has to be correct and can produce better product, so it needs to be analyzing before fabricate the mold. Material flow analysis should be running to the plastic product to ensure no defect and follow the characteristics from actual specification. This project is using Moldflow Plastic Insight software to analyze and investigate the effects of gate and the parameter on the product. UMP cardholder has been chosen as a subject of experiment. The result that use in this study are the fill time, time to freeze, the injection pressure, the clamping force, and also defects.